Learning in the library: A national study of youth services public library workers. Issue 6 (24th February 2021) - Colvin, Sharon; White, Annie M.; Akiva, Thomas
Abstract: Aims: This study aims to interrogate the occupational identity of youth services public library workers across the United States and to understand specifically how this study is related to the learning ecosystem. Public library workers, especially those who work specifically with youth, are underrepresented in academic literature. Method: We adapted an interview method that allows participants to explain how they think different stakeholders perceive their work and used it in a digital survey with 306 youth services public library workers. Results: Overall, the participants described their work as deeply connected to learning, specifically connecting people to resources, facilitating learning activities, and providing a space for learning. This reflects the evolving nature of public library services. Conclusion: Unfortunately, many library workers feel significant friction between their own understanding of their job and the views of outside stakeholders. We address this friction and its implications in our recommendations for future research and practice.